2017
DOI: 10.3390/ijtpp2020004
|View full text |Cite
|
Sign up to set email alerts
|

Transition Models for Turbomachinery Boundary Layer Flows: A Review

Abstract: Current models for transition in turbomachinery boundary layer flows are reviewed. The basic physical mechanisms of transition processes and the way these processes are expressed by model ingredients are discussed. The fundamentals of models are described as far as possible, with a common structure of the equations and with emphasis on the similarities between the models. Tests of models reported in the literature are summarized and our own test is added. A conclusion on the performance of models is formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 166 publications
(252 reference statements)
0
35
0
1
Order By: Relevance
“…It adopts the value of 1 in fully turbulent flow and 0 in laminar flow. In the locations of the boundary layer where turbulent structures start to be visible, intermittency begins to deviate from zero [51]. Together with an empirical transport equation for the transition momentum-thickness Reynolds number, the transition features of boundary layer are modeled [43].…”
Section: Visualisation Of Flow Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It adopts the value of 1 in fully turbulent flow and 0 in laminar flow. In the locations of the boundary layer where turbulent structures start to be visible, intermittency begins to deviate from zero [51]. Together with an empirical transport equation for the transition momentum-thickness Reynolds number, the transition features of boundary layer are modeled [43].…”
Section: Visualisation Of Flow Structuresmentioning
confidence: 99%
“…Energies 2017, 10, x FOR PEER REVIEW 18 of 24 intermittency begins to deviate from zero [51]. Together with an empirical transport equation for the transition momentum-thickness Reynolds number, the transition features of boundary layer are modeled [43].…”
Section: Visualisation Of Flow Structuresmentioning
confidence: 99%
“…Piotrowski et al [229,213] compared the PUIM [172,173] and the γ model of Lodefier & Dick [9] with the γ − Re θ model for wake-induced transition on the N3-60 cascade, which showed satisfactory results. Dick & Kubacki [167] compared the γ model, the k − k L − ω, Kubacki et al's model [182] and Kubacki & Dick's model [191] for the same case. They showed that the γ model performed best, since wakeinduced transition is dominated by the bypass transition, a conclusion similar to the one drawn by Pacciani et al [186].…”
Section: Comparative Studiesmentioning
confidence: 99%
“…The causes leading to the onset of the transition have not yet been fully clarified. However, four types of transition mechanisms have been recognized as the main factors responsible for the first order effects [37]. From an engineering point of view these explanations are more than sufficient and allow for a good comprehension and modeling of the phenomenon.…”
Section: Transition and Turbulence Modelingmentioning
confidence: 99%
“…From an engineering point of view these explanations are more than sufficient and allow for a good comprehension and modeling of the phenomenon. The types of mechanisms are the natural transition, the bypass transition, the separation-induced transition and the wake induced transition [37,38]. It is obvious that an accurate transition model must take into account all the aforementioned mechanisms.…”
Section: Transition and Turbulence Modelingmentioning
confidence: 99%